The impact of psychosocial interventions on condom and contraceptive use in LMICs: Meta-analysis of randomised controlled trials - Riedel, Elena M. C.; Turner, David T.; Kobeissi, Loulou Hassan; Karyotaki, Eirini; Say, Lale; Cuijpers, Pim (Global public health, 2020)
Inconsistent contraceptive use and risky sexual behaviour perpetuate the burden of sexually transmitted diseases, especially in low- and middle-income countries (LMIC). Psychosocial interventions (PSI) can contribute to change sexual behaviour, however, their overall effectiveness is unclear. We thus conducted a meta-analysis of the effectiveness of PSIs to increase condom and contraceptive use in LMICs. Seven databases were searched systematically for randomised trials comparing a PSI with a control condition. Risk ratios of 31 eligible studies were pooled in random-effects analyses for condom and contraceptive use and unprotected sex, using sensitivity analyses to further investigate the results. Risk of bias was assessed using the Cochrane tool, and heterogeneity and publication bias were assessed. PSIs increased condom use by about 6% at post-test and 8% at follow-up as compared to control conditions. Contraceptive use was increased by about 14% at post-test. There were no effects on unprotected sex. Results suggest that PSIs have the potential to increase contraceptive and, to a smaller degree, condom use in LMICs. The reliability of these results is partly limited by heterogeneity and the risk of publication bias. PSIs were further found to provide substantial benefits to the exposed populations beyond the targeted outcomes.